2018
DOI: 10.1016/j.molmet.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ERα action on muscle metabolism and insulin sensitivity – Strong enough for a man, made for a woman

Abstract: BackgroundThe incidence of chronic disease is elevated in women after menopause. Natural variation in muscle expression of the estrogen receptor (ER)α is inversely associated with plasma insulin and adiposity. Moreover, reduced muscle ERα expression levels are observed in women and animals presenting clinical features of the metabolic syndrome (MetSyn). Considering that metabolic dysfunction impacts nearly a quarter of the U.S. adult population and elevates chronic disease risk including type 2 diabetes, heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 182 publications
1
49
1
1
Order By: Relevance
“…The role of estrogen was not tested in our study, but there is abundant evidence that estrogens stimulate a range of transcriptional and post-translational changes that stimulate fatty acid utilization in the liver and skeletal muscle [48][49][50][51] and promote lipid storage in subcutaneous but not visceral fat in women [52]. The impact of estrogen on metabolism in females likely contributes to the relative protection from ectopic lipid accumulation found in MetS, but the adaptations to the HFS diet observed in our study occurred over a relatively short exposure when considered as a model of the chronic dietary intake of the Western diet in women.…”
Section: Discussionmentioning
confidence: 99%
“…The role of estrogen was not tested in our study, but there is abundant evidence that estrogens stimulate a range of transcriptional and post-translational changes that stimulate fatty acid utilization in the liver and skeletal muscle [48][49][50][51] and promote lipid storage in subcutaneous but not visceral fat in women [52]. The impact of estrogen on metabolism in females likely contributes to the relative protection from ectopic lipid accumulation found in MetS, but the adaptations to the HFS diet observed in our study occurred over a relatively short exposure when considered as a model of the chronic dietary intake of the Western diet in women.…”
Section: Discussionmentioning
confidence: 99%
“…The sexual dimorphic response specific to ER action has been associated with the development of or protection from certain diseases (e.g., metabolic syndrome and autoimmune diseases) [33][34][35][36]. As such, animal studies have demonstrated that exogenous exposures that inappropriately alter ER signaling can increase the relative risk for these diseases [37][38][39].…”
Section: The Role Of Genetic Sex In Mediating the Cellular Response Tmentioning
confidence: 99%
“…Die Östrogenrezeptordichte (Östrogenrezeptor-Alpha) der Skelettmuskulatur ist positiv assoziiert mit der Insulinsensitivität des Skelettmuskels. Bei Frauen mit metabolischem Syndrom sowie postmenopausalen Frauen ist die Östrogenrezeptorexpression der Skelettmuskulatur reduziert und nimmt im Verlauf der Postmenopause weiter ab [11,12]. Somit kommt es in der Folge zu einer Abnahme der Insulinsensitivität mit vermehrtem Rückfluss von Substraten und gesteigerter Substratverfügbarkeit an der Leber, was wiederum die DNL begünstigt.…”
Section: Pathophysiologie -Körperfettverteilung Und Lipidstoffwechselunclassified